Discord between Egyptian Agriculture Students’ and Employers’ Perceptions of the Importance of Various Skills in new Employees - Leah Thompson; J. Alex Pasternak; Ramjee Ghimire; D. Hashini Galhena Dissanayake; Nanda Joshi; Waleed Saleh; Paul Ebner (Journal of International Agricultural and Extension Education, 2021)
Unemployment remains high among Egyptian university graduates. This study aimed to identify demographic attributes that influence student perceptions of the importance of employability skills, as well as to measure concordance between employers versus student perceptions of the importance of employability skills. Egyptian university agriculture students and private sector employers completed a survey where they assessed their perceived importance of 35 skills. A multivariate linear regression model was used to measure the influence of student demographics in decision-making and concordance between employers and students were compared using Cohen's weighted Kappa. Student location was the most influential demographic that determined perceptions of the importance of employability skills. As a group, students possessed more intra-group concordance than employers, but concordance levels of all students were low when compared to employers. Our findings indicate that regardless of demographics, Egyptian agriculture university students are unaware of what is important to potential employers, meaning that students do not know which skills to focus on developing when searching for a job. Teaching students the skills that are most desired by employers contributes to Human Capital Theory because it improves the employability value of university graduates. Few studies have analyzed student demographics combined with student/employer concordance. This approach could assist future studies that aim to compare individual student and employer perceptions to each other.
Keywords: Egypt; employability; university agriculture students; concordance